Children Learning in Science, Direct Instruction, Virtual Laboratory Experiment, Phyphox, Literasi Sains, Digital - Sulman; Suarti; Suharti (Unnes Physics Education Journal, 2025)
This study aims to analyze the effectiveness of the Children Learning in Science (CLIS) model based on virtual laboratory experiments using the Phyphox application and the digital-based Direct Instruction model on students’ science literacy, as well as to compare the differences in effectiveness between the two. This study is a quasi-experimental study using a randomized pretest-posttest control group design. The study population included all seventh-grade students at MTsN 1 Makassar, with a sample of 64 students selected through multistage random sampling. Descriptive analysis results showed that the average science literacy score in the CLIS-Phyphox class was 62.23, while that of the digital-based Direct Instruction class was 53.15. The N-Gain test showed that the CLIS-Phyphox model fell into the “moderately effective” category (61.83%), while the digital-based Direct Instruction model fell into the “less effective” category (53.15%). Hypothesis testing using the Independent Sample T-Test yielded a Sig. (2-tailed) value of 0.026 (< 0.05), indicating a significant difference in effectiveness between the two models. It was concluded that the use of the CLIS model based on the Phyphox application is more effective in improving students’ science literacy compared to the digital-based Direct Instruction model.